In vitro mutation of White Kelampayan (neolamarckia cadamba) using Ethyl Methanesulfonate (EMS) - Delvino Disonneo, anak Dalin (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Neolamarckia cadamba or kelampayan is well known throughout the timber industry due to its fast growth rate. Kelampayan has many end uses that are not just limited to the timber industry. Through in vitro micropropagation, arise new ideas of producing new variation of white kelampayan. This study was attempted to develop new clones with improved traits of white kelampayan through in vitro mutagenesis using Ethyl methanesulfonate (EMS). In this study, calli and nodal segments were treated with three different concentrations of EMS, i. e. 0% (control), 0.1 %, 0.3% and 0.6% (v/v). Calli were exposed to EMS for 0.5,1 and 24 hours while nodal segments were exposed for 3 and 6 hours. Effects of EMS toward calli and nodes of kelampayan were identified in this study. For the calli, as the concentration and exposure duration increases, the percentage of survival and proliferation trended to decrease. Meanwhile for nodes, similar trend was observed on the survival percentage, number of leaves and plant height. Potential mutant cultivars with irregular leaves, red coloured leaves and early branching were also observed. It is recommended to do further studies on these potential mutants cultivars at genetic level by using DNA marker.